Survival and Outcomes of Lung‐Kidney and Lung‐Liver Transplants Using a Large National Cohort - John A. Treffalls; Kelly Pennington; Cassie C. Kennedy; Julie K. Heimbach; Carrie A. Schinstock; Mauricio A. Villavicencio; Sahar A. Saddoughi (Clinical Transplantation, 2026)
ABSTRACT Background We used a national cohort to compare post‐transplant outcomes of lung‐kidney and lung‐liver transplantation to isolated lung transplantation. Methods The United Network for Organ Sharing database was queried for all lung transplants performed from 1/1/2010‐9/30/2024. Heart‐lung and three‐organ transplants were excluded. Patients undergoing isolated lung transplantation were compared with those undergoing simultaneous lung‐kidney or lung‐liver transplantation. Cox proportional hazards models assessed factors associated with one and three‐year mortality. Temporal utilization trends were evaluated with linear regression. Results Among 33,656 lung transplant recipients, 33,358 (99.1%) underwent isolated lung, 137 (0.4%) underwent lung‐kidney, and 161 (0.5%) underwent lung‐liver transplantation. One‐year patient survival was lower for lung‐kidney (79.7%) and lung‐liver (82.6%) compared to lung (88.3%; log‐rank p < 0.001) but not at three years ( p = 0.101). Median survival was 6.3 (95% CI 6.2‐6.4) years for lung, 6.2 (95% CI 4.3‐10.0) years for lung‐kidney, and 9.5 (95% CI 4.8‐∞) years for lung‐liver ( log‐rank p = 0.392). Following multivariable Cox risk adjustment, lung‐liver was associated with increased one‐year mortality (HR, 1.64; 95% CI, 1.11‐2.41; p = 0.013) but not three‐year mortality (HR, 1.23; 95% CI, 0.90‐1.67; p = 0.187), while lung‐kidney was not associated with mortality at one ( p = 0.684) or three years ( p = 0.162). On linear regression, the incidence of lung‐kidney and lung‐liver both increased over the study period at a faster rate than lung transplantation. Conclusions Although lung‐kidney and lung‐liver had lower one‐year survival, three‐year survival was not different compared to isolated lung transplantation after risk adjustment. Given inferior short‐term outcomes, multiorgan recipients, particularly lung‐kidney, require more sensitive patient selection to ensure equitable access to abdominal allografts. However, these findings cautiously support the viability and increased utilization of multiorgan lung transplantation in carefully selected patients.